“I feel enthusiastic, when the homework is done well”: teachers’ emotions related to homework and their antecedents - Feiss, Christine; Hagenauer, Gerda; Moroni, Sandra (Frontiers in Education, 2023)
Emotions are an important factor influencing teaching behaviour and teaching quality. Previous studies have primarily focused on teachers' emotions in the classroom in general, rather than focusing on a specific aspect of teaching such as homework practice. Since emotions vary between situations, it can be assumed that teachers' emotions also vary between the activities that teachers perform. In this study, we therefore focus on one specific teacher activity in our study, namely homework practice. We explore teachers' emotions in homework practice and their antecedents. Methodologically, semi-structured interviews were conducted with 23 Swiss secondary school teachers teaching German and analysed using structuring qualitative content analysis. The results show that teachers experience a variety of positive and negative emotions related to homework practice, with positive emotions predominating. According to the teachers' reflections, the antecedents of their emotions could be attributed to the context (e.g., conditions at home), teacher behaviour and (inner) demands (e.g., perceived workload) and student behaviour (e.g., learning progress). Implications for teacher education and training are discussed.